An integrative redescription of Hypsibius dujardini (Doyère, 1840), the nominal taxon for Hypsibioidea (Tardigrada: Eutardigrada) - Gąsiorek, Piotr; Stec, Daniel; Morek, Witold; Michalczyk, Łukasz (Zootaxa, 2018)
A laboratory strain identified as “Hypsibius dujardini” is one of the best studied tardigrade strains: it is widely used as a model organism in a variety of research projects, ranging from developmental and evolutionary biology through physiology and anatomy to astrobiology. Hypsibius dujardini, originally described from the Île-de-France by Doyère in the first half of the 19th century, is now the nominal species for the superfamily Hypsibioidea. The species was traditionally considered cosmopolitan despite the fact that insufficient, old and sometimes contradictory descriptions and records prevented adequate delineations of similar Hypsibius species. As a consequence, H. dujardini appeared to occur globally, from Norway to Samoa. In this paper, we provide the first integrated taxonomic redescription of H. dujardini. In addition to classic imaging by light microscopy and a comprehensive morphometric dataset, we present scanning electron photomicrographs, and DNA sequences for three nuclear markers (18S rRNA, 28S rRNA, ITS-2) and one mitochondrial marker (COI) that are characterised by various mutation rates. The results of our study reveal that a commercially available strain that is maintained in many laboratories throughout the world, and assumed to represent H. dujardini sensu stricto, represents, in fact, a new species: H. exemplaris sp. nov. Redescribing the nominal taxon for Hypsibiidae, we also redefine the family and amend the definitions of the subfamily Hypsibiinae and the genus Hypsibius. Moreover, we transfer H. arcticus (Murray, 1907) and Hypsibius conifer Mihelčič, 1938 to the genus Ramazzottius since the species exhibit claws and eggs of the Ramazzottius type. Finally, we designate H. fuhrmanni as subjectively invalid because the extremely poor description precludes identifying neotype material.